Rasionalitas Antibiotik Pasien Bronkitis Akut Anak Dengan Metode Gyssens Di RSIA Zainab Kota Pekanbaru - Endri, Novtafia; Rahmawati, Ayu; Rahmawati, Noveri; Nesya, Nabilla Fadhia (LPPM, Universitas Muhammadiyah Riau, 2023)
According to WHO, as many as 13 million children in the world die every year and most of these deaths are in developing countries, where ISPA is one of the main causes of death by killing as many as 4 million children each year. Bronchitis ranks 6th out of 10 causes of death. However, Indonesia still has no reports on exact figures regarding this disease. This study aims to determine the accuracy of the use of antibiotics in pediatric patients with acute bronchitis based on the Gyssens method at RSIA Zainab Pekanbaru City. This type of research was non-experimental with data collection using a purposive sampling technique retrospectively. The results of the study based on a qualitative evaluation of the use of antibiotics in pediatric acute bronchitis patients at RSIA Zainab Pekanbaru City using the Gyssens method showed the quality of rational use of antibiotics found that 64 patients were declared rational ( category 0) and 5 patients were declared irrational. If possible further research regarding the rationality of using antibiotics in pediatric acute bronchitis patients at RSIA Zainab Pekanbaru City can be carried out using the DDD method or with a prospective approach so that monitoring of the patient's condition progress can be carried out from day to day.